A need for religion: insecurity and religiosity in the contemporary world - Molteni, Francesco (International studies in sociology and social anthropology, 2021)
"In A need for Religion: Insecurity and Religiosity in the Contemporary World Francesco Molteni tries to answer one of the broadest questions for scholars of religion: why is religiosity declining in developed countries? He does so by inspecting all the different nuances of the insecurity theory, which links the feeling of security typical of modern societies with the diminished need for religion as source of reassurance, support and predictability. in this respect, he notes that much of the evidence is far less clear than expected and that secularization processes are at an advanced stage only in a rather small group of worldwide countries"--